31.1k views
2 votes
Complete the square to transform the quadratic equation into the form (x – p)2 = q.

x2 - 6x - 8 = 6
A) (x - 6)2 = 9
B) (x - 3)2 = 23
C) (x - 6)2 = -9
D) (x - 3)2 = -23

User NCessity
by
4.7k points

2 Answers

2 votes

Answer:

For Usatestprep its D

Explanation:

i did the question on there

User Equidamoid
by
5.4k points
2 votes

Answer:

B

Explanation:

Given

x² - 6x - 8 = 6 ( add 8 to both sides )

x² - 6x = 14

To complete the square

add ( half the coefficient of the x- term )² to both sides

x² + 2(- 3)x + 9 = 14 + 9

(x - 3)² = 23 → B

User Michael Fox
by
5.6k points